Management of Paraphimosis in A Stray Dog - A Case Report - Thavani, K.L. (The Indian Journal of Animal Reproduction, 2021)
A one year old male stray dog was presented to Veterinary Dispensary, Cambay with of paraphimosis since last four hours with no history of recent mating. In spite of the severe paraphimosis the dog was healthy and active. The penis was engorged and congested with presence of several dark haemorrhagic areas. An edematous preputial band was constricting the penis, preventing its retraction into the preputial sheath. After treatment inflammation was subsided and animal was recovered uneventfully with no recurrence.